Common Sleep Disorders in Pregnancy. Issue 2 (6th August 2022) - Facco, Francesca L.; Chan, Megan; Patel, Sanjay R.
Abstract : Obstructive sleep apnea, insomnia, and restless legs syndrome are the most common sleep disorders seen in pregnancy. Abstract : Compared with men, women have a greater risk of sleep disorders and report higher rates of sleep disturbance. Hormonal and physiologic changes throughout the life span appear to influence a woman's ability to get a good night's sleep. Sleep disturbances are commonly reported during pregnancy, affecting more than one-half of all pregnancies and increasing as gestation progresses. The pervasiveness of sleep complaints during pregnancy may lead to a belief that these symptoms are normal or to be expected. Unfortunately, this perception may impede the accurate diagnosis of sleep disorders during this crucial time. Obstructive sleep apnea, insomnia, and restless legs syndrome are the most common sleep disorders in pregnancy. Sleep disruption in pregnancy can substantially worsen maternal quality of life and may be a risk factor for adverse pregnancy outcomes. This review outlines important considerations for obstetricians taking care of pregnant patients with sleep-related complaints.